Effects of dopamine D1 modulation of the anterior cingulate cortex in a fear conditioning procedure - Pezze, Marie A.; Marshall, H.J.; Domonkos, A.; Cassaday, Helen J. (Elsevier, 2015)
The anterior cingulate cortex (AC) component of the medial prefrontal cortex (mPFC) has been implicated in attention and working memory as measured by trace conditioning. Since dopamine (DA) is a key modulator of mPFC function, the present study evaluated the role of DA receptor agents in rat AC, using trace fear conditioning. A conditioned stimulus (CS, noise) was followed by an unconditioned stimulus (US, shock) with or without a 10s trace interval interposed between these events in a between-subjects design. Conditioned suppression of drinking was assessed in response to presentation of the CS or an experimental background stimulus (flashing lights, previously presented for the duration of the conditioning session). The selective D1 agonist SKF81297 (0.05 µg/side) or D1 antagonist SCH23390 (0.5 µg/side) was administered by intra-cerebral microinfusion directly into AC. It was predicted that either of these manipulations should be sufficient to impair trace (but not delay) conditioning. Counter to expectation, there was no effect of DA D1 modulation on trace conditioning as measured by suppression to the noise CS. However, rats infused with SKF81297 acquired stronger conditioned suppression to the experimental background stimulus than those infused with SCH23390 or saline. Thus, the DA D1 agonist SKF81297 increased conditioned suppression to the contextual background light stimulus but was otherwise without effect on fear conditioning.